Study on the Development of Fiber-Rich Noodles through the Substitution of Wheat Flour with Pregelatinized Tannia Flour - Putra, I Nengah Kencana; Suparthana, I Putu; Istri Sri Wiadnyani, Anak Agung (International Journal of Scientific Research and Management (IJSRM), 2024)
Traditional noodles are often criticized for their low fiber content, a component with numerous health benefits in preventing degenerative diseases. Tannia, a potential food source in Indonesia, is recognized for its richness in fiber.  This study evaluated the chemical properties, cooking quality, and sensory aspects of noodles made from a composite of wheat flour and pregelatinized tannia flour (PTF). PTF, obtained by boiling tannia tuber slices at a temperature of 95°C for 10 minutes, drying, mashing, and sieving using a 60-mesh sieve, was used to substitute some of the wheat flour in dry noodles production. Substitution levels ranged from 0% (control) to 30%. Results showed a significant impact on protein, carbohydrate, and crude fiber content, as well as color, cooking quality, and sensory properties. Crude fiber increased with substitution, but above 25%, noodles exhibited lower elasticity compared to the control. In conclusion, a 25% substitution of wheat flour with PTF produced noodles with higher crude fiber content, better cooking quality, and sensory properties comparable to control noodles (without substitution). Noodles with 25% substitution had a crude fiber content of 4.89%, while control noodles were at 3.84%